From Syndicates to Protocols: Rethinking Organized Crime in the Age of Cybercrime - Hartmann, Arthur (International Journal of Criminology and Sociology, 2025)
This article develops the concept of cyber-mediated organized crime to capture structural transformations driven by digital infrastructures, especially cryptocurrencies. Integrating functionalist theory (AGIL), Elias’s figurational sociology, and trust theory, it reconstructs how criminal formations adapt by substituting social embeddedness with cryptographic mechanisms. Empirical domains—ransomware, darknet markets, blockchain laundering—reveal how digital actors fulfill core functions of protection, coordination, and trust under pseudonymity and decentralization. Rather than replicating traditional hierarchies, these formations emerge as adaptive social systems shaped by functional differentiation and technological affordances. Their systemic resilience, despite evolving law enforcement strategies, underscores new modes of illicit governance and contestation.